Pengaruh Pendidikan Kesehatan Menggunakan Media Leaflet Terhadap Pengetahuan Orang Tua tentang Otitis Media Supuratif Kronik di Poliklinik THT RSUD Kabupaten Klungkung - komang suarningsih; I Gede Putu Darma Suyasa; Made Rismawan (Institute Teknologi dan Kesehatan (ITEKES) Bali, 2018)
Background: Chronic Suppurative Otitis Media is one of the health problems that can lead to ear hearing loss to be deaf, even life-threatening. Extension of Omsk can influence the understanding or the person's cognitive abilities, curiosity and want to learn about how to prevent complications Omsk. Problems are often encountered in is ignorance of parents on the prevention of complications and recurrence of OMSK Clinic Hospital in KlungkungObjective: the purpose of this study was to determine the effect of health education using the media leaflet to the knowledge of parents about Omsk Methods: This study uses an experimental approach to design pre One group pre test-posttest design. The sampling technique used is Non-Probability Sampling with saturated sampling technique. The population in this study were all parents who drove their children suffering from Omsk. Total sample of 60 respondents, gathering data using questionnaires.Results: parental knowledge about Omsk before being given health education most of which 37 (61.7%) less, parental knowledge about Omsk after being given health education most of which 35 (58.3%) good, Wilcoxon statistical test results signed rank test obtained P = 0.001 <α 0,05 showed no effect of health education using the media leaflet to the knowledge of parents about OMSKConclusion: prior knowledge of health education mostly less, after health education was mostly good analysis showed no effect of health education using leaflets media against parental knowledge about OMSK. Suggestion : Keywords: Health Education, Leaflet, Knowledge, Omsk